Pharmacological Inhibition and Genetic Knockdown of BCL9 Modulate the Cellular Landscape of Cancer-Associated Fibroblasts in the Tumor-Immune Microenvironment of Colorectal Cancer - Yang, Mengxuan; Wei, Zhuang; Feng, Mei; Zhu, Yuanyuan; Chen, Yong; Zhu, Di (Frontiers in Oncology, 2021)
Cancer-associated fibroblasts (CAFs) play a critical role in cancer progression and are activated in the tumor microenvironment (TME), but their pro-metastatic mechanisms are not defined. CAFs are abundant in colorectal cancer (CRC), where they are recruited from local tissue-resident fibroblasts or pericryptal fibroblasts and distant fibroblast precursors, and where they may promote metastasis-promoting communication is not clear. B-cell lymphoma 9/B-cell lymphoma 9-like (BCL9/BCL9L) is key transcription co-factor of β-catenin. We studied the TME of CRC with single-cell sequencing consequently found that Bcl9 depletion causes pro tumor effect of CAFs and the inhibition of abnormal activation of Wnt/β-catenin signal through Bcl9 depletion benefits T-cell-mediated antitumor immune responses. In summary, we demonstrate cell type and transcription difference of CAFs of BCL9 driven Wnt signaling affects cancer and immune surveillance, and the potential of targeting the Wntsignaling pathway via cancer immunotherapy.